DIFFICULTIES IN TEACHING ENGLISH LANGUAGE AND SOLUTIONS - Tojidinova Diyora (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: Teaching English as a second language can be challenging due to the complexity of grammar rules, pronunciation, vocabulary, idioms, and cultural differences. Additionally, teachers may face difficulties in motivating students, accommodating individual learning styles, and managing a diverse classroom. These challenges require patience, creativity, and flexibility in order to effectively teach English to non-native speakers. This article provides several possible solutions in order to solve difficulties in the process of teaching language.